Commercial Fraud Trials: Some Recent Developments - Clashfern, The Rt Hon Lord Mackay of (Journal of Malaysian and Comparative Law, 1993)
Text of the English Sultan Azlan Shah Law Lecture (organised by the Faculty of Law, University of Malaya and the British Council) delivered by the Rt Hon Lord Mackay of Clashfern, on 1 April 1993 in the presence of His Majesty, Sultan Azlan Shah, the Yang di-Pertuan Agong.